2017
DOI: 10.1177/1098612x17723773
|View full text |Cite
|
Sign up to set email alerts
|

Post-chemotherapy perforation in cats with discrete intermediate- or large-cell gastrointestinal lymphoma

Abstract: Objectives Gastrointestinal (GI) perforation is a well described complication of GI lymphoma in people, commonly occurring within days of initiation of chemotherapy. There are no studies documenting the prevalence of GI perforation in cats with intermediate- or large-cell GI lymphoma or whether it is associated with induction of chemotherapy. The objectives of this study were to document the prevalence and timing of post-chemotherapy perforation in cats with discrete GI masses caused by intermediate- or large-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0
2

Year Published

2020
2020
2025
2025

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 26 publications
0
4
0
2
Order By: Relevance
“…In veterinary medicine, one study suggested cats were at higher risk of perforation during endoscopy compared to dogs, while others have shown a lower incidence. [7][8][9]16 At this institution, a total of 254 endoscopies were performed in cats during the study period, while 1110 endoscopies were performed in dogs over the same timeframe. Furthermore, in the dogs, only one case of rupture post-ballooning a colonic stricture was reported, that is, a perforation rate of 0.09%.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In veterinary medicine, one study suggested cats were at higher risk of perforation during endoscopy compared to dogs, while others have shown a lower incidence. [7][8][9]16 At this institution, a total of 254 endoscopies were performed in cats during the study period, while 1110 endoscopies were performed in dogs over the same timeframe. Furthermore, in the dogs, only one case of rupture post-ballooning a colonic stricture was reported, that is, a perforation rate of 0.09%.…”
Section: Discussionmentioning
confidence: 99%
“…Lymphoma is the most common neoplasm of the cat, with the GIT being the most common location, accounting for up to 72% of newly diagnosed cases. 16 With surgical biopsies, the risk of intestinal wound dehiscence reported in cats was 3.5%. 17 Comparing with the reported endoscopic risk of 1.2%, then endoscopy remains the safer option for biopsy.…”
Section: Discussionmentioning
confidence: 99%
“…With the deepening of clinical research, the causes of GIL have become increasingly clear, including human immunodeficiency virus infection, immunosuppression, celiac disease, etc. As the clinical stage of the disease develops, patients will be accompanied by nausea, vomiting, hematemesis, abdominal pain and other uncomfortable conditions that are similar with those of other gastrointestinal diseases, easily causing misdiagnosis [17][18][19][20]. GIL originates from lymphoid tissue of the mucosa lamina propria or submucosa.…”
Section: Discussionmentioning
confidence: 99%
“…If present, these are often subtle, and include a progressive lack of appetite, lethargy, chronic diarrhea with or without melena, vomiting, and weight loss, leading to a poor general condition [8,9,11]. Sudden death may occur secondary to intestinal perforation and peritonitis [12].…”
Section: Introductionmentioning
confidence: 99%